PERAN DAN STRATEGI GURU DALAM MEMBENTUK AKHLAK SISWA: STUDI KASUS DI MIS MISHBAHUL AULAD KOTA SUKABUMI - Dadang Sahroni; Eki Agustin; Irsan Apriandinata; Rahmat; Farhan Haliman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the roles and strategies of teachers in shaping students’ moral character at MIS Mishbahul Aulad Sukabumi. The research employed a qualitative approach using a case study design to obtain an in-depth understanding of the phenomenon. Data were collected through participant observation, in-depth interviews, and documentation involving five teachers and fifteen sixth-grade students. The data were analyzed using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that teachers assume multiple roles, functioning as moral exemplars (qudwah hasanah), educators, facilitators, mentors, and motivators in fostering students’ character development. The strategies implemented include habituation of daily religious practices, teacher modeling in both behavior and worship, integration of moral values into classroom instruction, and the application of reward and punishment to reinforce discipline. However, several challenges were identified, particularly the inconsistency of moral reinforcement within the family environment and the influence of negative digital media content. These findings underline the necessity of strong collaboration between schools and parents in optimizing character education. This study contributes to the development of more contextual and integrative approaches to moral education in Islamic primary schools.